Assessment of the pulmonary toxic potential of nano-tobacco stem-pyrolyzed biochars. Issue 5 (10th April 2019) - Dong, C. D.; Lung, S. C. C.; Chen, C. W.; Lee, J. S.; Chen, Y. C.; Wang, W. C. V.; Chen, C. J.; Hung, C. M.; Lin, C. H.
Abstract : Despite the growing potential in various applications of nanobiochars, there are still concerns regarding their health effects. Abstract : Despite the growing potential in various applications of nanobiochars, there are still concerns regarding their health effects. In this study, we used a normal human in vitro model to investigate the possible toxic effects, including pulmonary toxicity, of epithelial exposure to nanobiochars. Nano-tobacco stem-pyrolyzed biochars (nTSBs), which are generated at 500 °C, were used to analyze their potential adverse effects on the lungs. Our results demonstrated that nTSBs can cause evident cytotoxic and genotoxic effects in epithelial cells by inducing ROS formation. nTSB exposure also led to the activation of inflammatory factors. Furthermore, decreases in transepithelial electrical resistance and zonula occludens proteins after exposure to nTSBs impaired the integrity of the epithelial barrier. Increases in oxidized α1-antitrypsin in BEAS-2B cells also suggested that nTSB exposure increases the risk of chronic obstructive pulmonary disease. However, all of these adverse responses were induced by high concentrations of nTSBs. Accordingly, the pulmonary toxic potential of nTSBs occurring at high concentrations is likely not the same as that occurring at more realistic outdoor exposure concentrations. Collectively, our results indicate that the risk of nTSB toxicity is low when nTSBs are used as raw materials in commercial applications.